1987
DOI: 10.2307/1590876
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Maduramicin against Ionophore-Tolerant Field Isolates of Coccidia in Broilers

Abstract: Maduramicin ammonium was given at 2.5-8 ppm in the feed to broilers experimentally infected with coccidia recently isolated from broiler farms where ionophores had been used for several years. Infection pressure varied from mild to severe in five trials: mortality in unmedicated controls ranged from 0 to 59%, intestinal lesion scores were high, and weight gain was depressed by the infections. The cultures of Eimeria were partly resistant to ionophores: birds medicated with monensin at 100-121 ppm had only mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In contrast, investigations (Ruff et al, 1985;Ryley, 1980;Abbas et al, 2008aAbbas et al, , 2009 indicate that Eimeria isolates resistant to one ionophore are resistant to the others. A high degree of cross resistance has been reported among maduramicin, monensin, salinomycin, narasin, and lasalocid (Raether and Paeffgen, 1989), but a number of reports (McDougald et al, 1987;Bedrnik et al, 1989;Yadav and Gupta, 2001;Abbas et al, 2008a) are available stating that maduramicin was effective in controlling isolates of Eimeria resistant to other ionophores. McDougald (1993) suggested that the knowledge of differences in efficacy of different ionophores might be useful for the proper control of coccidiosis.…”
Section: Cross Resistancementioning
confidence: 99%
“…In contrast, investigations (Ruff et al, 1985;Ryley, 1980;Abbas et al, 2008aAbbas et al, , 2009 indicate that Eimeria isolates resistant to one ionophore are resistant to the others. A high degree of cross resistance has been reported among maduramicin, monensin, salinomycin, narasin, and lasalocid (Raether and Paeffgen, 1989), but a number of reports (McDougald et al, 1987;Bedrnik et al, 1989;Yadav and Gupta, 2001;Abbas et al, 2008a) are available stating that maduramicin was effective in controlling isolates of Eimeria resistant to other ionophores. McDougald (1993) suggested that the knowledge of differences in efficacy of different ionophores might be useful for the proper control of coccidiosis.…”
Section: Cross Resistancementioning
confidence: 99%
“…Attempts to prevent outbreak of coccidiosis in pheasants using anticoccidial drugs have been reported (JurkoviAE c et al, 1982;Norton, 1982Norton, , 1986McQuistion, 1987;Vanparijs et al, 1990). However, the long-term use of anticoccidial drugs may lead to the proliferation of drug-resistant protozoans, as seen in chicken farms (Jeffers, 1977;Duh & Wang, 1986;Saitoh et al, 1986;McDougald et al, 1987;Kawazoe & Fabio, 1994;Williams, 1998). This will result in increased difficulties in preventing future coccidiosis (Chapman, 1982(Chapman, , 1997McDougald & Seibert, 1998).…”
Section: Introductionmentioning
confidence: 99%